Universitas Muhammadiyah Sidoarj An Analysis of the Implementation of the Internal Quality Assurance System (SPMI) and Its Impact on Enhancing Faculty Competence at STAI Ali bin Abi Thalib Surabaya: Analisis Implementasi Sistem Penjaminan Mutu Internal (SPMI) dan Dampaknya Pada Peningkatan Kompetensi Dosen di STAI Ali bin Abi Thalib Surabaya - ElMuslim, Dani; Churrahman, Taufik (Indonesian Journal of Innovation Studies, 2026)
General Background Internal Quality Assurance System (IQAS) implementation serves as a crucial foundation for institutional development in higher education. Specific Background At STAI Ali bin Abi Thalib Surabaya, the system follows the PPEPP cycle to manage academic quality standards. Knowledge Gap However, the direct execution of this operational cycle and its actual influence on fulfilling faculty competency standards remain under-examined in Islamic higher education context. Aims This study analyzes IQAS implementation and its role in fulfilling lecturer competencies. Results Findings reveal that while IQAS execution directly improves professional research output and inter-unit social collaboration, overall faculty standard compliance reaches only partial levels due to administrative adaptation challenges. Novelty This paper provides a contextual evaluation connecting PPEPP operational stages directly to specific lecturer competency achievements in Middle Eastern-integrated Islamic colleges. Implications Strengthening continuous control and quality improvement mechanisms is essential to fully align faculty performance with national standards. Key Findings Highlights implementation of the PPEPP cycle improves faculty research productivity and inter-unit collaboration. compliance with faculty qualification standards remains partial due to administrative adaptation gaps. continuous quality control mechanisms are essential to meet full institutional educational standards. Keywords : Internal Quality Assurance System, PPEPP Cycle, Lecturer Competency, Islamic Higher Education, Quality Control